Nitrate decontamination through functionalized chitosan in brackish water. (20th August 2016) - Appunni, Sowmya; Rajesh, Mathur P.; Prabhakar, Sivaraman
Graphical abstract: Highlights: TEACCB has been prepared for the first time. TEACCB has the highest nitrate removal capacity among reported chitosan adsorbents. TEACCB selectively removes nitrate in the presence of chloride and sulphate. Removal of nitrate from brackish water through column shows the efficiency of bead. Abstract: N, N, N -Triethyl ammonium functionalized cross-linked chitosan beads (TEACCB) was prepared by alkylation of glutaraldehyde cross-linked chitosan beads to remove nitrate from brackish water. Physico-chemical characteristics of TEACCB were analyzed using FTIR, SEM, EDAX, TGA, DTA, BET surface area, swelling ratio and pHzpc . The maximum nitrate removal capacity of TEACCB was 2.26 meq/g and is higher than other reported chitosan based adsorbents. Nitrate removal ratio in the presence and absence of common anions like chloride and sulphate demonstrated the selectively of TEACCB towards nitrate. The kinetic data of nitrate removal fitted well with the pseudo-second-order kinetic model. The thermodynamic parameters indicated that nitrate removal could be spontaneous and exothermic in nature. TEACCB was reused with 100% efficiency after regenerating with 0.05 N HCl. Column study was carried out to remove nitrate from brackish water. These results are very significant to develop TEACCB based nitrate removal technology with great efficiency.